Investigating Turkish Primary School Teachers’ Beliefs About L1 Writing Instruction Through Attribution Theory: Process-Oriented versus Product-Oriented Perspectives - Omer Faruk Tavsanli (SAGE Open)
The purpose of the current research is to investigate the primary teachers’ epistemological and pedagogical beliefs related to how to improve students’ L1 (mother tongue) writing skills. Furthermore, the participating teachers’ attributions regarding their students writing achievement levels were examined. A basic qualitative research design was preferred in the current study. The study was conducted with six primary school teachers. The participants were categorized as teachers who adapted the process-based writing or product-based writing. According to the current study results, it is clearly stated that teachers’ beliefs related to the writing instruction were differentiated according to the preferred writing instruction philosophy, and their attributions regarding their students’ writing success were different in the context of Attribution Theory [AT]. This current study’s findings reveal important and timely information on how to teach writing to primary graders that extends beyond the U.S. or European context.